Search for colour singlet and colour reconnection effects in hadronic Z decays at LEP - Dova, María Teresa (2004)
A search is performed in symmetric 3-jet hadronic Z-decay events for evidence of colour singlet production or colour reconnection effects. Asymmetries in the angular separation of particles are found to be sensitive indicators of such effects. Upper limits on the level of colour singlet production or of colour reconnection effects are established for a variety of models.